Early modern trauma : Europe and the Atlantic World - Peters, Erin; Richards, Cynthia (Early modern cultural studies (Lincoln, Neb.), 2021)
"With contributions by established experts in the fields of history, language, and literature, as well as early career scholars, Early Modern Trauma explores what trauma-seen through an analytical lens-can reveal about the early modern period and, conversely, what conceptualizations of psychological trauma from the early modern period can tell us about trauma theory itself"--